Pola Hubungan Kausalitas Variabel Penentu Partisipasi Petani Terhadap Efektivitas Program AUTP di Kabupaten Lampung Selatan - Siti Bherliana Maharani Setiawati; Muhammad Abdurrokhim; Muhammad Farandika Akbar; Puja Triandini; Yudika Ester Kejutini Sigiro (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aimed to (1) analyze the factors influencing farmers' participation in the Rice Farming Insurance Program (AUTP) and (2) examine the causal relationships between participation determinants and the effectiveness of the AUTP program in South Lampung Regency, Indonesia. The research employed a quantitative explanatory approach using path analysis on data collected from 85 rice farmers in Palas District. The results revealed that program knowledge (β = 0.145) and the intensity of extension assistance (β = 0.077) were the primary drivers of farmers' participation. In contrast, physical characteristics, such as farm size and farming experience, had no significant effect on participation. A key finding showed that the level of participation (β = 0.186) acted as an intervening variable, mediating the influence of antecedent factors on program effectiveness. In addition, program effectiveness was significantly influenced by the adequacy of insurance coverage (β = 0.258) and program knowledge (β = 0.247). These findings suggest that the effectiveness of the AUTP in disaster-prone areas depends not only on financial subsidies but also on farmers' insurance literacy and the quality of extension support. However, program sustainability remains challenged by the complexity of digital registration procedures and delays in claim verification, highlighting the need for better policy synchronization and administrative improvements.